Evolutionary dynamics in Drosophila subobscura: analyses of life history traits and microsatellite loci during laboratory adaptation - Simões, Pedro (2010)
Tese de doutoramento em Biologia (Biologia Evolutiva), apresentada à Universidade de Lisboa através da Faculdade de Ciências, 2007